The rescue - Sparks, Nicholas (New York : Warner Books, 2000)
A volunteer fireman and a single mother join forces to find the woman's son who has been lost in a storm. While searching for the boy, the two adults find themselves increasingly close.
740
Accelerated Reader AR
Keywords: Fire fighters -- Fiction; Single mothers -- Fiction; Children with disabilities -- Fiction; Edenton (N.C.) -- Fiction; Domestic fiction; Love stories